2010
DOI: 10.1007/s00586-010-1517-4
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic stabilization adjacent to single-level fusion: Part II. No clinical benefit for asymptomatic, initially degenerated adjacent segments after 6 years follow-up

Abstract: Progression of degeneration is often described in patients with initially degenerated segment adjacent to fusion (iASD) at the time of surgery. The aim of the present study was to compare dynamic fixation of a clinically asymptomatic iASD, with circumferential lumbar fusion alone. 60 patients with symptomatic degeneration of L5/S1 or L4/L5 (Modic ≥ 2°) and asymptomatic iASD (Modic = 1°, confirmed by discography) were divided into two groups. 30 patients were treated with circumferential single-level fusion (SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 40 publications
3
72
1
1
Order By: Relevance
“…However, this study also found a 9.1% incidence of degeneration in the more distant levels. 17,18,23 In a systematic review of literature, Zhou et al found that the incidence of adjacent-segment degeneration was statistically lower in patients treated by dynamic stabilization compared with solid fusion. There was a tendency for a lower incidence of ASD following dynamic stabilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this study also found a 9.1% incidence of degeneration in the more distant levels. 17,18,23 In a systematic review of literature, Zhou et al found that the incidence of adjacent-segment degeneration was statistically lower in patients treated by dynamic stabilization compared with solid fusion. There was a tendency for a lower incidence of ASD following dynamic stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported on an acceleration of the process of degeneration in the spinal segment adjacent to a level of prior arthrodesis that may result in poor clinical outcome and sometimes a need for further surgery. 18 Multiple dynamic stabilization systems are currently available, and all use a variety of motion-preserving technologies ranging from semirigid rods to ball-and-socket joints. 2 The use of dynamic stabilization for the treatment of ASD at the rostral end of an instrumented arthrodesis might therefore reduce further progression of the degenerative process by decreasing hypermobility and stresses in adjacent levels.…”
mentioning
confidence: 99%
“…Compared with static fixation, numerous types of dynamic fixators have been developed to preserve the mobility of the transition segments and to reduce the occurrence of the junctional problem [21][22][23]. Among them, the dynamic neutralization system (Dynesys) is one of the commonly used dynamic fixators [12,24]. The Dynesys system consists of titanium alloy pedicle screws, cannulated polycarbonate urethane (PCU) spacers, and tensioned cords made of polyethylene terephthalate (PET).…”
Section: Discussionmentioning
confidence: 99%
“…inclusion criteria (2,3,6,(11)(12)(13)(14)(15)(16)(17)(19)(20)(21)(22)(23)(26)(27)(28)(29)(30)33,34,36,37,(41)(42)(43)(45)(46)(47) (Figure 1). For the possible duplicate studies (31&40,14&23,13&15), only the data from the trial with the longest follow-up were used for estimating the incidence of ASD.…”
Section: Zhou Zj Et Al: Can Posterior Dynamic Stabilization Reduce Tmentioning
confidence: 99%